The feeling of being watched: lived Confucianism and theatricality in Kuo Pao Kun's mid-1980s monodramas. Issue 2 (2nd April 2020) - Rae, Paul
ABSTRACT: The first plays Kuo Pao Kun (1939–2002) wrote after being released from detention in 1980 coincided with a concerted effort by the Singapore government to formalise the Confucian basis upon which it claimed that Singapore society and its increasing economic success were built. Kuo was no traditionalist, but The Coffin is Too Big for the Hole (1985), and No Parking on Odd Days (1986) can be interpreted as expressing — and producing – the lived experience of the ordinary in ways that are informed by a Confucian sensibility. In this article, I contextualise these plays with reference to the Singapore government's "Confucian turn" in the 1980s, and then demonstrate how they provided an intermediate domain between the state and the individual for exploring the classical Confucian concerns of moral action and ritual within a rapidly modernising society.